Barotrauma and Successful Release of Fish Caught in Deep Water - Elizabeth A. Staugler; Holly Abeels; Angela Collins; Shelly Krueger; Kai Lorenzen (EDIS)
If you catch a fish you are not going to keep, help it survive and get back to the deep! Throwing back your unwanted catch is good practice because healthy released fish can live to grow and reproduce, which benefits the fish population and the future of fisheries. But deepwater fish can have trouble getting back where they came from without a little assist from the angler. This 4-page fact sheet written by Betty Staugler, Holly Abeels, Angela Collins, Shelly Krueger, and Kai Lorenzen and published by the UF/IFAS Florida Sea Grant College Program describes barotrauma, a problem that, if left untreated, will kill otherwise perfectly healthy fish, and explains a few quick and simple methods to relieve fish suffering from barotrauma and help them get back home healthy and strong. https://edis.ifas.ufl.edu/sg160